Improved Electrochemical Performance of 0.5Li2MnO3·0.5LiNi0.5Mn0.5O2 Cathode Materials for Lithium Ion Batteries Synthesized by Ionic-Liquid-Assisted Hydrothermal Method - Xiang, Yanhong; Jiang, Youliang; Liu, Saiqiu; Wu, Jianhua; Liu, Zhixiong; Zhu, Ling; Xiong, Lizhi; He, Zeqiang; Wu, Xianwen (Frontiers in Chemistry, 2020)
Well-dispersed Li-rich Mn-based 0.5Li2MnO3·0.5LiNi0.5Mn0.5O2 nanoparticles with diameter ranging from 50 to 100 nm are synthesized by a hydrothermal method in the presence of N-hexyl pyridinium tetrafluoroborate ionic liquid ([HPy][BF4]). The microstructures and electrochemical performance of the prepared cathode materials are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and electrochemical measurements. The XRD results show that the sample prepared by ionic-liquid-assisted hydrothermal method exhibits a typical Li-rich Mn-based pure phase and lower cation mixing. SEM and TEM images indicate that the extent of particle agglomeration of the ionic-liquid-assisted sample is lower compared to the traditional hydrothermal sample. Electrochemical test results indicate that the materials synthesized by ionic-liquid-assisted hydrothermal method exhibit better rate capability and cyclability. Besides, electrochemical impedance spectroscopy (EIS) results suggest that the charge transfer resistance of 0.5Li2MnO3· 0.5LiNi0.5Mn0.5O2 synthesized by ionic-liquid-assisted hydrothermal method is much lower, which enhances the reaction kinetics.